Protective effect of feruloylated oligosaccharides on dextran sulfate sodium‐induced ulcerative colitis in rats - Lingxiao Gong; Linlin Hu; Hongna Wang; Rui Chen; Jing Wang (Food Frontiers, 2022)
Abstract Feruloylated oligosaccharides (FOs), comprising ferulic acid and arabinoxylans, have already been proved to possess beneficial properties that are closely related to the pathogenesis of ulcerative colitis (UC). This study aims at investigating the protective effect of FOs on chronic UC rats and its regulatory mechanisms. The study demonstrated that FOs alleviated the chronic UC through a combination of pharmacological mechanisms, including antioxidant, inhibiting the inflammatory response, improving the gut barrier and modulating the overall structure of gut microbiota. FOs showed immunomodulatory effect by downregulating the relative expression of proinflammatory cytokines IL‐1β, IL‐6, and TNF‐α in colon tissue. In addition, the FOs exhibited antioxidant activity by increasing SOD activity but reducing MDA content, iNOS activity and NO content. In terms of intestinal barrier, FOs inhibited gut barrier damages by enhancing tight junction protein expression (claudin‐3, occluding, and ZO‐1) and recovering the ultrastructure of intestinal barrier. Moreover, FOs also could partially restore the intestinal biodiversity in the DSS‐induced UC rats and increased the species richness of beneficial bacteria such as Akkermansia and Roseburia. These findings provide novel insights into the FOs‐mediated alleviation of chronic UC and will facilitate the preventive strategies for chronic UC.